Supporting young immigrants in their transition from school to work? A staff perspective on challenges of vocational integration classes - Reinke, Hannes [Verfasser]; Goller, Michael [Verfasser] (My University, 2022)
„The implementation of successful measures to support immigrants' integration in cultural, social, and economic life can be considered as one of today's greatest challenges for many societies. This is especially true for adolescent immigrants who have not yet been able to finish education or gain qualifications relevant to joining the labour market. That is why many receiving countries have developed and implemented special programmes that aim at supporting immigrants' integration by facilitating their employability. Unfortunately, not much is known about the process of implementing these programmes or about how education systems, schools, and teachers are dealing with the new situation and target group. In this contribution, the implementation, development, and challenges of German Vocational Integration Classes (VIC), as an example of comparable programmes in the EU, are investigated to address this research gap. The paper considers the following exploratory research questions: (a) What challenges have been experienced by teachers and social workers in the implementation of VIC as well as in the integration of immigrants into the labour market in recent years? (b) How can these challenges be met in the long run and how should VIC be developed to better achieve its aims?“ (authors‘ abstract; BIBB-Doku)
Keywords: P 1.5 Migranten; P 1.1 Jugendliche; S 3.1.1 Berufsvorbereitende Bildungsgänge; G 1.3.2.2 Übergänge; 370; Flüchtling; Jugendlicher; Berufsvorbereitung; Berufliche Integration; Lehrer